Dampak Perkembangan Teknologi dan Digitalisasi dalam Bisnis Syariah Analisis Sosiologi Hukum terhadap Perubahan pada Praktik Transaksi Keuangan Islam - Dahlia, Dea; Srimauludiyah; Arifin, Tajul; Abdal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to analyze the impact of digitization of technological developments on Sharia business activities regarding Islamic financial transactions. Analyzing in the sociology of law regarding changes in Islamic financial transactions in the era of digitalization. With the development of digitalization technology, there are significant changes in aspects of life, especially in Islamic finance. The nature of this research is qualitative research with an analytical descriptive approach, and legal sociology analysis, the method used is the collection of a number of data through library research. In the analysis of legal sociology, it understands how the community and Islamic economic actors adapt to these changes and how to interpret changes in sharia with the digitalization of technological advances. In Sharia business and Islamic finance with the digitalization of technological developments there are many changes to these changes, there is a need to comply with sharia principles such as respecting the integrity of Islamic values. This discussion provides insight into how Islamic businesses can thrive in the digital age without compromising religious values. Keywords: Islamic business digitalization, sociology of law, Islamic financial transactions